Interrupted time series analysis of pediatric hospital acquired malnutrition risk score implementation in hospitalized Thai children - Thitichaya Leesurapong; Suchaorn Saengnipanthkul; Prapassara Sirikarn; Phanthila Sitthikarnkha; Leelawadee Techasatian; Rattapon Uppala (Scientific Reports)
Abstract Hospital-acquired malnutrition (HaM) is a major issue in pediatric care, leading to increased morbidity. The Pediatric Hospital-Acquired Malnutrition (PHaM) risk score was developed to improve the early identification and nutritional management of at-risk pediatric patients. This study evaluated the impact of PHaM implementation in a tertiary pediatric hospital, focusing on early identification, clinical intervention rates, and patient outcomes. A quasi-experimental interrupted time series (ITS) design was employed, involving three phases: pre-implementation, implementation (staff training), and post-implementation (routine use of PHaM). Pediatric patients aged 1 month to 18 years, admitted for at least 72 h, were included. Data were analyzed to assess changes in the prevalence of HaM, management practices, and clinical outcomes. A total of 1,658 pediatric patients were admitted during study periods, with 377 patients (201 cases in pre-implementation, 33 cases in implementation, and 143 cases in post-implementation periods) qualifying for PHaM screening. Median patient age ranged from 45 to 56.5 months, with no significant differences across the three phases. The implementation of the PHaM risk score led to a significant decrease in the prevalence of HaM, from 25.9% pre-implementation to 12.1% during implementation and 6.3% in the post-implementation phase. Nutritional interventions increased from 20.9% pre-implementation to 33.3% during implementation and 35.0% post-implementation. Additionally, patients experiencing weight loss without intervention significantly decreased from 28.9% pre-implementation to 12.1% during the implementation and 4.9% post-implementation. The ITS analysis showed immediate reductions in the prevalence of HaM, weight loss without intervention, and health care-associated infections with increased nutritional intervention. Hospital costs decreased significantly post-implementation, as did the length of hospital stay. However, there were no significant long-term trend changes for most outcomes assessed. The PHaM risk score effectively improved immediate key clinical outcomes, reducing HaM, infections, and hospital costs. However, sustaining long-term improvements requires additional strategies for early malnutrition screening. Trial registration: TCTR20220705004 (04/07/2022).